Application of Warm Compresses on Reducing Dysmenorrhea Pain Levels - Nindawi, Nindawi; Elisa Crhistiana; Mukhlish Hidayat; Maisaroh (Jurnal Vokasi Kesehatan, 2025)
Dysmenorrhea is lower abdominal cramping pain during menstruation which is usually experienced for 1-2 days every month. Dysmenorrhea can be treated non-pharmacologically, one of which is done warm compresses, with warm compresses can increase muscle relaxation and reduce pain due to stiffness and provide a sense of warmth. The purpose of this study was to analyze the effect of giving warm compresses on reducing dysmenorrhea pain levels. This study uses pre-experimental (one-group pre-post test design). The population and sample were all adolescent girls who experienced dysmenorrhea pain with a total sampling technique of 30 respondents. Data collection using Close Ended Questioner Numeric Rating Scale (NRS). Data were analyzed univariate by measuring the degree of dysmenorrhea pain before and after warm compresses and bivariate to determine the effect of warm compresses on dysmenorrhea pain using the Wilcoxon statistical test method <0.05. It was found that before being given a warm compress most respondents experienced severe pain as many as 16 (53%), after being given a warm compress most experienced mild pain as many as 15 (50%) in adolescent girls. Wilcoxon statistical test results obtained Asymp. Sig. <0,01. There is an effect of giving warm compresses to adolescent girls. This effect needs to be applied independently by respondents in overcoming dysmenorrhea pain by doing warm compresses. Health workers provide education about references to complementary dysmenorrhea pain management (warm compresses) which have minimal side effects.